2012
DOI: 10.1186/1471-2334-12-110
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and societal burden of varicella zoster virus in the Netherlands

Abstract: BackgroundVaricella and herpes zoster are both caused by varicella zoster virus (VZV) infection or reactivation and may lead to complications associated with a (severe) societal burden. Because the epidemiology of VZV-related diseases in the Netherlands remains largely unknown or incomplete, the main objective of this study was to study the primary care incidence, associated complications and health care resource use.MethodsWe investigated the incidence of VZV complications in the Dutch general practitioner (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 30 publications
4
30
2
2
Order By: Relevance
“…The most frequently found unique data source was on seroprevalence ( n  = 52) [17–68], followed by hospitalisation ( n  = 39) [23, 27, 40, 69–104], primary care ( n  = 27) [7, 8, 23, 27, 74, 76, 7881, 97, 99, 102, 104117], mortality ( n  = 15) [11, 23, 27, 7476, 79, 80, 84, 91, 97, 118–121], and incidence of reported varicella cases through mandatory surveillance ( n  = 14) (Table 1) [5, 26, 27, 40, 79, 80, 101, 116, 122–127]. Varicella community incidence was estimated from 43 seroprevalence data sources from 16 countries [17–27, 2941, 4447, 4954, 5762, 64, 65, 68], primary care incidence from 17 PCI data sources from 8 countries [23, 74, 76, 79, 80, 99, 101, 102, 104106, 109, 110, 112, 114, 124, 126], hospitalisation incidence from 18 HI data sources from 10 countries [23, 69–73, 75, 76, 79–81, 84, 87, 90, 91, 94, 102, <...>…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently found unique data source was on seroprevalence ( n  = 52) [17–68], followed by hospitalisation ( n  = 39) [23, 27, 40, 69–104], primary care ( n  = 27) [7, 8, 23, 27, 74, 76, 7881, 97, 99, 102, 104117], mortality ( n  = 15) [11, 23, 27, 7476, 79, 80, 84, 91, 97, 118–121], and incidence of reported varicella cases through mandatory surveillance ( n  = 14) (Table 1) [5, 26, 27, 40, 79, 80, 101, 116, 122–127]. Varicella community incidence was estimated from 43 seroprevalence data sources from 16 countries [17–27, 2941, 4447, 4954, 5762, 64, 65, 68], primary care incidence from 17 PCI data sources from 8 countries [23, 74, 76, 79, 80, 99, 101, 102, 104106, 109, 110, 112, 114, 124, 126], hospitalisation incidence from 18 HI data sources from 10 countries [23, 69–73, 75, 76, 79–81, 84, 87, 90, 91, 94, 102, <...>…”
Section: Resultsmentioning
confidence: 99%
“…Varicella community incidence was estimated from 43 seroprevalence data sources from 16 countries [17–27, 2941, 4447, 4954, 5762, 64, 65, 68], primary care incidence from 17 PCI data sources from 8 countries [23, 74, 76, 79, 80, 99, 101, 102, 104106, 109, 110, 112, 114, 124, 126], hospitalisation incidence from 18 HI data sources from 10 countries [23, 69–73, 75, 76, 79–81, 84, 87, 90, 91, 94, 102, 103], and one data source was used to estimate mortality in 31 countries [11] (Table 2). Data on all four outcomes was only available for six countries (Belgium, France, Italy, the Netherlands, Spain and the UK).…”
Section: Resultsmentioning
confidence: 99%
“…2,8,27,28,[32][33][34][35][36][37][38][39] Gender differences in the incidence of herpes simplex add strong support to the hypothesis that females have a differing response to latent viral infection and that this may account for their increased risk compared with men. 16 Studies conducted in numerous settings, and with various designs, have indicated an association between age and increasing zoster incidence.…”
Section: Sociodemographic Factorsmentioning
confidence: 86%
“…Although annual incidence rates were presented for 11 studies [47, 9, 11, 17, 1922], we focused on three studies as they reported the annual incidence data specifically for the ≥65 age group while also reporting incidence over a sufficiently long time period so as to perform linear best fit curve. The studies used to estimate the incidence rates were Leung et al [6], Toyama et al [7] and MacIntyre et al [4] which reported HZ incidence rates for the US, Japan and Australia respectively and was adjudged to present a reasonable picture of the expected HZ burden in high-income country setting.…”
Section: Methodsmentioning
confidence: 99%